BILMIX: a new approach to restore the size polydispersity and electron density profiles of lipid bilayers from liposomes using small‐angle X‐ray scattering data. Issue 1 (6th December 2019) - Konarev, Petr V.; Petoukhov, Maxim V.; Dadinova, Liubov A.; Fedorova, Natalia V.; Volynsky, Pavel E.; Svergun, Dmitri I.; Batishchev, Oleg V.; Shtykova, Eleonora V.
Abstract : The use of the BILMIX program to model small‐angle X‐ray scattering data of model membranes and deliver a description of the lipid bilayer electron density and vesicle size distribution is presented. Abstract : Small‐angle X‐ray scattering (SAXS) is one of the major tools for the study of model membranes, but interpretation of the scattering data remains non‐trivial. Current approaches allow the extraction of some structural parameters and the electron density profile of lipid bilayers. Here it is demonstrated that parametric modelling can be employed to determine the polydispersity of spherical or ellipsoidal vesicles and describe the electron density profile across the lipid bilayer. This approach is implemented in the computer program BILMIX . BILMIX delivers a description of the electron density of a lipid bilayer from SAXS data and simultaneously generates the corresponding size distribution of the unilamellar lipid vesicles.